Interactions between callus cultures of European beech, indigenous ascomycetes and derived fungal extracts - Hendry, S J (The New phytologist, 1993)
Ascomycete fungi from the Xylariaceae and Diatrypaceae responded in three distinct ways when grown in dual culture with callus material of beech (Fagus sylvatica L.). Growth of the putative weak pathogens Biscogniauxia nummularia (Bull.) O. Kuntze and Eutypa spinosa (Pers.) Tul. & C. Tul. was stimulated whilst the saprotrophs Ustulina deusta (Hoffm.) Lind. and Xylaria polymorpha (Pers.) Grev. were unaffected by the presence of callus. Sapwood-colonizing fungi displayed a range of responses, with Diatrype stigma (Hoffm.) Fr. being unaffected, Diatrype disciformis (Hoffm.) Fr. stimulated, and Hypoxylon fragiforme (Pers.: Fr.) Kickx and 'Hypoxylon purpureum' inhibited by the presence of callus. Changes in morphology were evident in many of the fungi during interactions, with yeast-like forms being produced by those members of the Xylariaceae which have been recognized as endophytes. Reciprocally, high concentrations of cell free extracts of some of the Xylariaceous fungi resulted in necrosis or inhibition of callus growth, while at sub-lethal concentrations marked stimulation of growth was evident. The importance of these results with respect to pathogenicity testing and elucidation of the biology of tree-fungus interactions is discussed